?THE USE OF SESBANIA AS AN ALTERNATIVE SOURCE OF UREA-N FOR BR-J J RICE (Biological Sciences - PJSIR, 1995)
A field trial was conducted to evaluate the performance or Sesbania and /1:01/(1 manures as alternative sources or urca-N in producing higher yield or BR-II rice. Sesbania (inoculated with Bradvrhizobium inoculant) treatment resulted in the highest rice yield of 4363 kg/hu with a yield benefit or 44%, increase over control. The increase in rice yield was 32'Yt,due to urea and 31% 1'01' Sesbania (uninoc.). Azol!a manuring could not give signilkantly higher yield because ofinsufficient biomass production due to elevated temperature prevailing during the growth period. Scsbania manuring enriched soil fertility by increasing organic matter level and P, K and S availability in soils.